PAPILLARY THYROID CARCINOMA, FOLLICULAR AND TALL CELL VARIANT, ARISING FROM A MATURE TERATOMA - Magpusao , Marielle Claudette; Ibarra Co, Juan Maria (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE The malignant transformation of monodermal ovarian teratoma into a tall cell variant of papillary thyroid carcinoma is exceptionally rare. We report its first case in Southeast Asia wherein a 33-year-old Filipino female presented with a 5-month history of painless, progressively enlarging abdomen. Ultrasonography showed a large well-circumscribed, cystic mass with floating internal echoes occupying the pelvoabdominal region and an ovarian new growth. The patient then underwent exploratory laparotomy with left salpingo-oophorectomy, right oophorocystectomy, and endometriotic implant fulguration. Histopathology revealed papillary thyroid carcinoma, follicular and tall cell variant arising from a mature teratoma with a TTF-1+/CK7+/CK20-immunophenotype. The patient is currently undergoing surveillance with no signs of recurrence and has been advised of total thyroidectomy. Since clinical practice guidelines have yet to be established concerning this tumor, existing literature was further reviewed focusing on the appropriate diagnostics and management. Generally, an excellent prognosis is expected.